PENGARUH REKRUTMEN TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA HOTEL BINTANG LIMA PEKANBARU - Nurhayati, Tini; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research was conducted at the Hotel Bintang Lima Pekanbaru, the study aims to determine the effect of recruitment to employee performance. Recruitment as an independent variable (X), while the performance of the employee as the dependent variable (Y).Samples are 26 respondents, all employees of a Hote Bitang Lima Pekanbaru.data obtained from the questionnaire and further processed to then be tested with statistics through SPSS program. Results of calculation of the coefficient of determination is 0,731. That is to say, the recruitmen affects the performance of employees amounted to 73,1%.Keywords : Recruitment, Employee Performance, Hotel Bintang Lima Pekanbaru